2016
DOI: 10.1186/s40064-016-1781-9
|View full text |Cite
|
Sign up to set email alerts
|

Canadian CT head rule and New Orleans Criteria in mild traumatic brain injury: comparison at a tertiary referral hospital in Japan

Abstract: We compared Canadian computed tomography (CT) head rule (CCHR) and New Orleans Criteria (NOC) in predicting important CT findings in patients with mild traumatic brain injury (TBI). We included 142 consecutive patients with mild TBI [Glasgow coma scale (GCS) 13–15] who showed at least one of the risk factors stated in the CCHR or the NOC. We introduced two scores: a Canadian from the CCHR and a New Orleans from the NOC. A patient’s score represented a sum of the number of positive items. We examined the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…When correctly applied, both the CCHR and NOC lead to slightly more than 50% of patients being scanned with computerized tomography (CT) of the head [21]. The CCHR guidelines are constructed chiefly to rule out intracranial hemorrhage requiring intervention and have been validated with a 100% detection rate [21][22][23]. The SNC guidelines aim to detect all intracranial hemorrhages and have been prospectively validated as safe [18].…”
Section: Introductionmentioning
confidence: 99%
“…When correctly applied, both the CCHR and NOC lead to slightly more than 50% of patients being scanned with computerized tomography (CT) of the head [21]. The CCHR guidelines are constructed chiefly to rule out intracranial hemorrhage requiring intervention and have been validated with a 100% detection rate [21][22][23]. The SNC guidelines aim to detect all intracranial hemorrhages and have been prospectively validated as safe [18].…”
Section: Introductionmentioning
confidence: 99%
“…11 This study focused on CCHR, 4 which can be used for minor head trauma in patients with GCS scores between 13 and 15, and evaluated its diagnostic power to determine patients with minor head trauma who should be evaluated with head CT. Mata-Mbemba et al compared CCHR and NOC in 142 patients to identify important CT findings among patients with GCS scores from 13 to 15 and found that CCHR had lower sensitivity, higher specificity, and higher accuracy than NOC (sensitivity, 89.8% vs. 97.9%; specificity, 24.7% vs. 9.7%; and accuracy, 47.2% vs. 40.1%). 12 In this study, the overall performance of CCHR was superior to that of NOC in patients with minor head trauma. A study by Kavalci et al comparing CCHR and NOC reported that the sensitivity, specificity, PPV and NPV of CCHR were 100%, 0%, 42%, and 100%, respectively, in patients with a GCS score of 13.…”
Section: Discussionmentioning
confidence: 58%
“…[ 16 ] There is a lot of controversy in the use of CT in head trauma, especially in MHI. Different guidelines are followed in different parts of the world for taking CT.[ 6 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 ] There is a lot of controversy in the use of CT, especially in MHI. [ 6 7 ] This study was intended to estimate the rate of CT positivity and to define the criteria for doing head CT in our patient population with special emphasis on MHI.…”
Section: Introductionmentioning
confidence: 99%